Psychosocial risks among junior high school teachers: Associations with mental workload and work stress in Makassar - Yurah, Alisyah; Ibrahim, Hasbi; Adha, Andi Syamsiah; Mallapiang, Fatmawaty (SAMATA JOURNAL OF PUBLIC HEALTH SCIENCE, 2026)
Psychosocial risks are increasingly recognized as important non-physical occupational hazards, yet evidence on their simultaneous relationship with mental workload and work stress among teachers remains limited; this study addresses that gap in junior high schools in Makassar. This study aimed to determine the relationship between psychosocial risk, mental workload, and work stress among teachers. A quantitative cross-sectional study was conducted among 123 teachers selected through census sampling at SMPN 23 Makassar and SMPN 19 Makassar. Psychosocial risk was assessed using the Copenhagen Psychosocial Questionnaire (COPSOQ), mental workload using the National Aeronautics and Space Administration Task Load Index (NASA-TLX), and work stress using the Depression Anxiety Stress Scales-21 (DASS-21). Data were analyzed using univariate analysis and Spearman’s rank correlation test. Psychosocial risk was significantly associated with mental workload (p=0.016; r=0.218), indicating a weak positive correlation, and with work stress (p<0.001; r=0.546), indicating a moderate positive correlation. Higher psychosocial risk was therefore associated with greater mental workload and work stress. These findings support the need for school-based occupational health interventions focusing on balanced workload distribution, stronger social support, clearer role organization, and policies that promote teachers’ mental health and safer working conditions.